14. ANALYZE SOME RELATED FACTORS TO THE TREATMENT ADHERENCE TO DRUG-RESISTANT TUBERCULOSIS OF PATIENTS AT HANOI LUNG HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Background: Drug-resistant Tuberculosis, especially multi-drug-resistant Tuberculosis is a potentially fatal form of tuberculosis that is difficult to treat and is resistant to most anti-Tuberculosis drugs, which are currently the most potent drugs such as Isoniazid and Rifamipicin.Objectives: Analyze some related factors to the treatment adherence to drug-resistant tuberculosis of patients at Hanoi Lung Hospital, in 2018Methods: Cross-sectional surveyResults: The rate of patient's adherence to treatment rate was 40.1%. The factors associated with statistical significance with adherence to treatment for drug-resistant Tuberculosis include: Factors belonging to the patients (marital status, education level, knowledge of drug-resistant Tuberculosis, comorbidities, risk behavior risk such as drinking beer/alcohol, smoking tobacco/waterpipe and drugs using), family and social factors, health service factors and drugs/treatment regimens (p
Keywords: Drug-resistant Tuberculosis; related factors; adherence to treatmen